Translation Shift Analysis in Subtitle of To All The Boys I’ve Loved Before (2018) (Conference on English Language Teaching, 2025)
This research sets out to examine the various types of shifts and the causal factors that appear in the subtitles of the To All the Boys I’ve Loved Before (2018) film. Employing a qualitative descriptive method, the study draws on Catford’s (1995) theory of translation shifts, which distinguishes between level shift and category shift. The category shift are further classified into structure shift, class shift, unit shift, and intra-system shift. Data were gathered using documentation techniques and analyzed through the lens of Catford’s theoretical framework. The analysis uncovered a total of 407 instances of translation shifts: 28 were identified as level shifts, while the remaining 379 fell under category shifts, broken down into 175 unit shifts, 116 structure shifts, 67 intra-system shifts, and 21 class shifts. These shifts primarily occurred due to grammatical and structural differences between the SL (English) and the TL (Indonesian), along with the need to adjust meaning to ensure that the message remains natural and culturally appropriate for the target audience. The findings of this study are expected to contribute to the field of translation studies, particularly in deepening the understanding of how translation shifts function within the context of film subtitling